Knowledge, perceptions, and management of symptoms of hormonal imbalance among adolescent girls in selected schools in Ghana: a qualitative exploratory study - Zakariah-Akoto, Sawudatu; Abuaku, Benjamin; Egbi, Godfred; Klu, Bismark Edem Kofi; Kyei-Baafour, Eric; Ofori, Michael Fokuo; Ahorlu, Collins Stephen; Yeboah-Manu, Dorothy (Frontiers in Reproductive Health, 2024)
IntroductionAdolescent girls are more sensitive to hormonal imbalance with major impact on their nutritional, reproductive, physical, psychosocial, and academic wellbeing. This study explored adolescent girls’ knowledge and perceptions of causes and management of symptoms of hormonal imbalance.Materials and methodsUsing a qualitative approach, focus group discussions were conducted with 116 assented in-school adolescent girls aged 10–19 years between 3rd and 19th October 2022. Two urban and two rural communities in two regions were purposively selected for the study. Using a convenient sampling approach, participants were recruited from Upper Primary, Junior, and Senior High schools. Data was analyzed thematically using both inductive and deductive approaches.ResultsSenior High School participants had a fair understanding of hormonal imbalance in both regions. Symptoms were perceived to include headaches, heavy and painful periods, and pimples, most of which participants alluded to experiencing. Perceived causes included natural process of adolescent growth, consumption of unhealthy diets, use of cosmetics and medications. Perceived reproductive effects included infertility, pregnancy disorders, breastfeeding challenges, and low sexual drive. Physiological effects included extreme fatigue, loss of appetite and impaired growth. Psychosocial and academic effects included mood swings/irritability, low self-esteem, poor inter-personal relationship, poor concentration in class and irregular school attendance. Female relatives and friends were mostly consulted for advice. Self-medication, dietary modification, physical activities, and personal hygiene were adopted to manage perceived symptoms. Self-medication was common, but physical activities and dietary modification were also adopted by most participants to manage symptoms.ConclusionIt is recommended that Ghana Education Service should formally incorporate hormonal-related issues into its School Health Education Programmes to enhance knowledge, attitudes, and management among adolescent girls at all levels of education.